Voci dal mondo per Primo Levi In memoria, per la memoria - Dei, Luigi (Studi e saggi, 2007)
Twenty years ago a unique figure in the history of our country returned dramatically to the world of the "drowned", one of the spectral "saved" who had found the strength to testify the dramas of the twentieth century: Primo Levi. On the twentieth anniversary of his death, Firenze University Press has decided to revive his lesson with a tribute that is not intended as a celebration, but rather as a pause for refection in which we can listen again to the words of this great writer, dissected and scrutinised the world over, generating germs of memory hopefully as universal as the mathematical and geometrical signs and the chemical formulas he so loved. Voci dal mondo per Primo Levi. In memoria, per la memoria edited by Luigi Dei, a lecturer in physical chemistry at the University of Florence, consists of fifteen short essays contributed by a polyhedric group of writers from various parts of the world and of different educational and professional backgrounds. Review: La Rassegna Mensile di Israel Interview with Ustation.it